Surgical site infection following cesarean section in a general hospital in Kuwait: trends and risk factors. (2019) - Alfouzan, W.; Al Fadhli, M.; Abdo, N.; Alali, W.; Dhar, R.
Abstract: Surgical site infections (SSI) are a significant cause of post-surgical morbidity and mortality. The objectives of this study were to determine the prevalence of SSI and identify risk factors for infections following cesarean section (CS). A prospective study of SSI after CS was carried out from January 2014 to December 2016 using the methodology of the American National Nosocomial Infection Surveillance System. Suspected SSIs were confirmed clinically by the surgeon, and or, by culture. Seven thousand two hundred thirty five CS were performed with an overall SSI prevalence of 2.1%, increasing from 1.7% in 2014 to 2.95% in 2016 ( P = 0.010). Of 152 cases of SSI, the prevalence of infection was 46.7% in women ⩽30 years and 53.3% in women >30 years ( P = 0.119). Of 148 culture samples from as many women, 112 (75.7%) yielded growth of microorganisms with 42 (37.5%) of isolates being multi-drug resistant (MDR). Women who did not receive prophylactic antibiotics (35.5%) developed SSI more often than those who did ( P < 0.0001). These findings suggest that emergency CS and inappropriate antibiotic prophylaxis are risk factors for developing SSI. In the light of the emergence of MDR bacteria there is a need to implement revised prophylactic antibiotic policy as part of antimicrobial stewardship to decrease SSI rates.